Occupational risks in Veterinary Medicine in Latin America and the Caribbean. A review - Tarabla, Héctor D. (2017)
Veterinarians are exposed to physical, biological, chemical and radiation hazards. The objective of this study was to review work accidents (WA) and diseases (WD), risk factors and perceptions, use and disposal of personal protective equipment (PPE) in Veterinary Medicine in Latin America and the Caribbean. Frequency of work accidents for veterinarians is very high, with the resulting loss of working days. WAs vary according to animal species. The most frequent WAs were bites, scratches, running over/imprisonment by animals and wounds caused by sharp objects. The most frequently diagnosed zoonosis in large animal clinics was brucellosis, while dermatophytosis and scabies in small animal practices. Injuries of an ergonomic nature include musculoskeletal injuries (spine and joints). Clinical practice was not perceived as a high-risk activity, although most WAs occurred in those instances. Frequency of use of PPE varied depending on the different professional activities and populations surveyed. Gloves were the most used PPE, while the lack of use of protective goggles or face masks was very evident. There were no associations between risk perception and use of PPE. In general, both were higher among women and young veterinarians. The final destination of disposable material was often inappropriate. Risk perception and adoption of good practices in itinere was greater along main roads than along rural roads, but WAs were more frequent in the latter. WAs and WDs should not be assumed to be a natural occurrence not requiring any action. Behaviors and attitudes in the veterinary practice need to change; working conditions must be improved; awareness should be raised with new generations of professionals; and veterinarians should comply with their social duty as public health agents.